Structural and compositional changes of bamboo fibers during super-heated steam treatment improved mechanical properties of polypropylene/bamboo biocomposite - Yamashiro, Keisaku (2021)
Structural and compositional changes of bamboo fibers, which were prepared through super-heated steam (SHS) treatment at normal pressure and fine grinding, were investigated by infra-red spectroscopy, thermogravimetry, viscosity-average molecular weight (Mv) measurement, and X-ray fluorescence analysis. SHS-treated Moso bamboo resulted in preferential decomposition of hemicellulose without any decrease in the Mv of cellulose crystalline. The SHS-treated bamboo was easily ground to obtain various short bamboo fibers (sBF) suitable for conventional melt processing of composites with polypropylene. The sBF showed good melt-processability and contributed to the mechanical performance of the composites moldings, resulting in 290% increases in flexural modulus.